Time Dilation in Interstellar Missions: A Systematic Literature Review on Relativistic Effects and Technological Solutions - Rara Rara; Nadiar Pertiwi; Hamdi akhsan; Melly Ariska (Universitas Hamzanwadi, 2025)
Interstellar exploration faces fundamental challenges due to the time dilation effects of Einstein's theory of relativity. This review presents a comprehensive analysis of the principle of time dilation, implications for interstellar missions, as well as cutting-edge technologies that utilize this principle. The Systematic Literature Review (SLR) method with PRISMA approach was applied, resulting in 42 relevant articles that met the inclusion criteria. The review results show that: (1) the effects of time dilation pose significant challenges in interstellar mission planning, particularly in the aspects of navigation, communication, and crew biology; (2) the development of cutting-edge technologies such as the Breakthrough Starshot relativistic vehicle, high-precision atomic clocks, and autonomous AI systems offer innovative solutions to overcome these challenges; (3) the integration of relativity understanding with these advanced technologies opens up new opportunities to realize interstellar exploration in the coming decades. These findings confirm that although time dilation is a major obstacle, the development of revolutionary technologies can turn it into a supporting factor in the realization of interstellar missions.